PENGARUH ADITIF EKSTRAK DAUN PEPAYA (Carica papaya L.) PADA AIR MINUM TERHADAP KUALITAS FISIK DAGING AYAM JOPER - C. F. B., GIRSANG; SRIYANI, N. L. P.; DEWI, G. A. M. K. (Majalah Ilmiah Peternakan, 2022)
This study aims to determine the effect of adding papaya leaf extract (Carica papaya L.) on drinking water to physical quality of Joper chicken meat. This study used a completely randomized design (CRD) with four treatmen- ts and four replications. Every unit was contained 3 Joper chickens. The treatments were drinking water without papaya leaf extract (P0), drinking water with 25 ml of papaya leaf extract in 1 liter of water (P1), drinking water with 30 ml of papaya leaf extract in 1 liter of water (P2), drinking water with 35 ml papaya leaf extract in liters of water (P3). The variables observed were pH, color, water holding capacity, cooking loss, and weep loss. The results showed that the addition of papaya leaf extract had a significant effect (P<0.05) on the physical quality of Joper chicken meat. Papaya leaf extract decreased the physical quality of Joper chicken meat in terms of water holding ca- pacity, cooking loss, and weep loss in P2 and P3 treatments. However, this papaya leaf extract treatment improves the quality of the flesh color to become brighter. The conclusion of this study is the addition of papaya leaf extract in drinking water affects the physical quality of Joper chicken meat compare without papaya leaf extract. The treat- ment that gave the best results was P1 treatment with the addition of 25 ml of papaya leaf extract.